The initiator of neuroexcitotoxicity and ferroptosis in ischemic stroke: Glutamate accumulation - Fan, Genhao; Liu, Menglin; Liu, Jia; Huang, Yuhong (Frontiers in Molecular Neuroscience, 2023)
Glutamate plays an important role in excitotoxicity and ferroptosis. Excitotoxicity occurs through over-stimulation of glutamate receptors, specifically NMDAR, while in the non-receptor-mediated pathway, high glutamate concentrations reduce cystine uptake by inhibiting the System Xc-, leading to intracellular glutathione depletion and resulting in ROS accumulation, which contributes to increased lipid peroxidation, mitochondrial damage and ultimately ferroptosis. Oxidative stress appears to crosstalk between excitotoxicity and ferroptosis, and it is essential to maintain glutamate homeostasis and inhibit oxidative stress responses in vivo. As researchers work to develop natural compounds to further investigate the complex mechanisms and regulatory functions of ferroptosis and excitotoxicity, new avenues will be available for the effective treatment of ischaemic stroke. Therefore, this paper provides a review of the molecular mechanisms and treatment of glutamate-mediated excitotoxicity and ferroptosis.